2007
DOI: 10.1111/j.1365-2036.2007.03384.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐line triple therapy with levofloxacin for Helicobacter pylori eradication

Abstract: SUMMARY BackgroundAt present, the efficacy of proton pump inhibitor-clarithromycin-amoxicillin regimen is relatively low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 54 publications
3
50
0
Order By: Relevance
“…The present study showed an eradication rate of 79% and 69% with the STT and 87% and 80% with the LBT in PP and ITT analysis respectively. Gisbert et al [10] studied the efficacy of LBT as the first line treatment of H. pylori and found eradication rates of 88% and 84% under PP and ITT analysis respectively, which are comparable to the results of our study. Schrauwen et al [24] from the Netherlands found that therapy with the levofloxacin regimen was very effective in the eradication of H. pylori.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…The present study showed an eradication rate of 79% and 69% with the STT and 87% and 80% with the LBT in PP and ITT analysis respectively. Gisbert et al [10] studied the efficacy of LBT as the first line treatment of H. pylori and found eradication rates of 88% and 84% under PP and ITT analysis respectively, which are comparable to the results of our study. Schrauwen et al [24] from the Netherlands found that therapy with the levofloxacin regimen was very effective in the eradication of H. pylori.…”
supporting
confidence: 82%
“…Vaira et al [20] reported a compliance rate of 94% in patients receiving STT. Gisbert et al [10] reported similar adherence to treatment in his study among patients receiving both STT and LBT.…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…These favorable results have been confirmed in vivo, indicating that most of the patients with both metronidazole and clarithromycin resistance are cured with the levofloxacin-based regimen [52,94,100] . A combination of a PPI, amoxicillin and levofloxacin, as a first-line regimen, has been associated with favorable results, with mean eradication rates of about 90% [95,[101][102][103][104][105][106] . Subsequently, other authors studied this same regimen in patients with one previous eradication failure, also reporting exciting results, with H pylori cure rates ranging from 60% to 94%…”
Section: Rbc Tetracycline and Metronidazolementioning
confidence: 99%